Peran Ergonomi Keperawatan dalam Meningkatkan Kesehatan dan Kinerja Perawat - Nadila, Putri; Safrudin, M bachtiar; Aprillia, Widya; Dwi Purnamasari, Rizka; Sarda Amelia, Salsabila; Candra Maulani, Kamila (Pustaka Galeri Mandiri, 2025)
The nursing profession carries a high risk of occupational health problems due to non-ergonomic working conditions, such as musculoskeletal complaints and physical fatigue. According to the World Health Organization (WHO, 2022), more than one-third of nurses worldwide experience such disorders caused by improper working postures and excessive physical workloads. This study employs a literature review method to analyze various national and international studies concerning the implementation of nursing ergonomics and its impact on nurses’ health and performance. The findings indicate that ergonomic applications using observational methods such as RULA, REBA, and OWAS effectively reduce the risk of Musculoskeletal Disorders (MSDs). Meanwhile, the use of physiological biomonitoring technologies like ECG helps monitor body responses to workload. In addition to physical aspects, psychological well-being and workplace environment significantly affect nurses’ performance. Therefore, comprehensive nursing ergonomics play a vital role in enhancing safety, efficiency, and the overall quality of nursing care.